Design of Claystone Selection as Surface Material for Mine Haul Roads at Pit PQRT, Berau Regency, East Kalimantan Province, Indonesia - Adi Kurniawan Tiranda; Busthan Azikin (Journal of Geology and Exploration, 2025)
Administratively, the study area is located in Samburakat, Gunung Tabur District, Berau Regency, East Kalimantan Province, Indonesia. Geographically, it lies between 117°34′30″–119°33′00″ E and 02°17′30″–02°19′30″ S. This study investigates the mechanisms responsible for the formation of undulating sections on mine haul roads, identifies suitable material sources based on Unconfined Compressive Strength (UCS) values, and evaluates their economic feasibility as surface course materials for mine roads. The methodology integrates field mapping of undulating road sections, material source mapping, frequency analysis of undulating areas, rainfall observation, and lithological characterization within the pit area. Laboratory testing of the physical and mechanical properties of the identified lithologies was conducted to assess their bearing capacity and performance under wet conditions. The results demonstrate that haul road surfaces constructed using sandstone are highly susceptible to the development of undulating deformation due to meteoric water infiltration, which significantly reduces material bearing capacity. In contrast, claystone exhibits superior performance as a road surface material owing to its impermeable characteristics, higher cohesion, and greater resistance to moisture-induced degradation, thereby maintaining subgrade stability and supporting haulage loads more effectively. UCS test results indicate that PQ claystone exhibits the highest strength (13,730 kPa), followed by QR claystone (11,720 kPa) and R claystone (5,028 kPa). Sandstone shows comparatively lower performance under wet conditions despite relatively high UCS values, with QR sandstone (13,550 kPa), PQ sandstone (10,670 kPa), and R sandstone (2,940 kPa). Material extraction strategies were optimized based on proximity to haul roads and UCS values to enhance operational efficiency and economic viability. The findings confirm that claystone, particularly PQ and QR units, is the most suitable material for mine haul road surface construction in the study area The methodology integrates field mapping of undulating road sections, material source mapping, frequency analysis of undulating areas, rainfall observation, and lithological characterization within the pit area. Laboratory testing of the physical and mechanical properties of the identified lithologies was conducted to assess their bearing capacity and performance under wet conditions. The results demonstrate that haul road surfaces constructed using sandstone are highly susceptible to the development of undulating deformation due to meteoric water infiltration, which significantly reduces material bearing capacity. In contrast, claystone exhibits superior performance as a road surface material owing to its impermeable characteristics, higher cohesion, and greater resistance to moisture-induced degradation, thereby maintaining subgrade stability and supporting haulage loads more effectively. UCS test results indicate that PQ claystone exhibits the highest strength (13,730 kPa), followed by QR claystone (11,720 kPa) and R claystone (5,028 kPa). Sandstone shows comparatively lower performance under wet conditions despite relatively high UCS values, with QR sandstone (13,550 kPa), PQ sandstone (10,670 kPa), and R sandstone (2,940 kPa). Material extraction strategies were optimized based on proximity to haul roads and UCS values to enhance operational efficiency and economic viability. The findings confirm that claystone, particularly PQ and QR units, is the most suitable material for mine haul road surface construction in the study area